PENGELOLAAN PEMBELAJARAN PROGRAM LIFE SKILL DI SANGGAR KEGIATAN BELAJAR KABUPATEN SUKOHARJO - M.Si, Supardo; Santosa, Sigit (Manajemen Bisnis Syariah, 2012)
The purpose of this research are description wish to: 1) How study planning in Gallery Group Of Learning District Sukoharjo?; 2) How organization in Gallery Group Of Learning District Sukoharjo?; 3) How study process in Gallery Group Of Learning District Sukoharjo?; 4) How out study put in Gallery Group Of Learning District Sukoharjo?; 5) How out come in SKB District Sukoharjo?. This research approach is qualitative research, that is research about data collected and expressed in the form of words compiled in sentence. Research approach applies phenomenology. Research subject is leading Gallery Group Of Learning and teacher nursemaid. Data collecting method applies in-depth interview, observation, and documentation. Analysis data analytical technique interactive.. authenticity of data applies trianggulation technique. Result of research that is: 1)   Study planning done by teacher nursemaid, include; covers activitys: has calendar of academic, maps allocation of time, compiles program year, program semester, compiles execution plan of study, syllabus, evaluation plan, supplies life efficiency, prepares source of learning, prepares class, teaching aid, and presentation student, assessment and reporting result of student learning; 2) Increasingly good management of organization, hence would increasingly good also institution, for example head Gallery Group Of Learning responsible as educator, manager, evaluator, administrator, supervisor, leader, innovator, and motivator. While learning nursemaid to have fundamental duty, function, responsibility plans, executes, and evaluates study; 3) execution of Study in SKB District Sukoharjo refers to study planning and organization according to fundamental duty and its(the function is each, collaboration teacher humanity nursemaid, head Gallery Group of Learning, and stakeholders; 4) Graduate (out put) Gallery Group Of Learning District Sukoharjo shows result satisfying, every year pass 100% and its(the value above average specified by government, graduate masters teaching matter and has efficiency of life according to requirement of student and public; 5) Document of Graduate is archival carefully, order, and at any times required for inspection can be shown; 5) Pass result fulfilling quality standard specified by government to affect is positive at graduate (out put), some of students passing the can create employment self though its(the scale is small, and partly other permeated in corporate world and industrial world. All graduate is nothing that out of job. Key Word : life skill, Learning , Gallery Group Of Learning